Frequency of Alcohol Use among Year 1 University Students and Its Affecting Factors - Sevinç Sütlü; Firdevs Savi Çakar (Addicta: The Turkish Journal on Addictions)
In most of today’s societies, alcoholic beverages are seen as a routine part of the social environment. It is overlooked that alcohol is an addictive psychoactive substance and constitutes a significant global disease burden. It is known that adolescents constitute the most risky group in society in terms of starting addictive substances. The aim of this study was to determine the prevalence of alcohol use and the factors affecting it among first-year students of a university in Türkiye. The population of the descriptive cross-sectional study consisted of 9050 first-year students. The sample size was calculated as 955. Nine hundred eighty-one students participated. Of the participants, 39.4% stated that they had tried an alcohol product at least once, and 14.9% stated that they were still using it. Male gender of the student, previous or current employment, higher education level of the mother, and having alcohol users in their families were found to be factors that increased the risk of alcohol use (p = .001; p = .000; p = .000). The determination of the age of alcohol experi- mentation as 9 shows that intervention programs need to be brought down to the basic education level. The gender norms and family role modeling in alcohol use increase the risk of alcohol use among young people. First of all, campaigns should be organized to raise public awareness that alcohol use is not a part of social participation and that it is not only a harmful habit but also an addiction. Multi-stakeholder studies should be carried out involving university students who are in the age group with the highest usage rate.